Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jocn.2021.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between multiple sclerosis and neuromyelitis optica spectrum disorders by multiparametric quantitative MRI using convolutional neural network

Abstract: Multiple sclerosis and neuromyelitis optica spectrum disorders are both neuroinflammatory diseases and have overlapping clinical manifestations. We developed a convolutional neural network model that differentiates between the two based on magnetic resonance imaging data. Thirty-five patients with relapsing-remitting multiple sclerosis and eighteen age-, sex-, disease duration-, and Expanded Disease Status Scale-matched patients with anti-aquaporin-4 antibody-positive neuromyelitis optica spectrum disorders we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…This was a retrospective case-control study comprising 66 subjects matched for age and sex (Table 1), including 30 patients (6 males and 24 females, 51.43 ± 8.02 years old) with a diagnosis of RRMS according to the revised McDonald criteria 2017 (Thompson et al, 2018), 18 patients (2 males and 16 females, 52.67 ± 16.07 years old) with a diagnosis of NMOSD according to Wingerchuk's criteria 2015 (Wingerchuk et al, 2015), and 19 healthy controls (6 males and 13 females, 51.47 ± 9.25 years old). The population of this study overlapped with that of a previously published study (Hagiwara et al, 2021). All patients with NMOSD were anti-AQP4 IgG seropositive, whereas all patients with RRMS were seronegative.…”
Section: Participants and Clinical Assessmentsmentioning
confidence: 99%
“…This was a retrospective case-control study comprising 66 subjects matched for age and sex (Table 1), including 30 patients (6 males and 24 females, 51.43 ± 8.02 years old) with a diagnosis of RRMS according to the revised McDonald criteria 2017 (Thompson et al, 2018), 18 patients (2 males and 16 females, 52.67 ± 16.07 years old) with a diagnosis of NMOSD according to Wingerchuk's criteria 2015 (Wingerchuk et al, 2015), and 19 healthy controls (6 males and 13 females, 51.47 ± 9.25 years old). The population of this study overlapped with that of a previously published study (Hagiwara et al, 2021). All patients with NMOSD were anti-AQP4 IgG seropositive, whereas all patients with RRMS were seronegative.…”
Section: Participants and Clinical Assessmentsmentioning
confidence: 99%
“…Convolutional neural network (CNN) is a type of deep learning known to be useful for image tasks, with its architecture resembling that of the human visual cortex 128,129 . In recent years, deep learning, particularly CNN, has gained substantial popularity in the MRI field for image reconstruction, image quality improvement, image transfer, disease detection, tissue segmentation, and classification 130–142 …”
Section: Analyzing Multiparametric Mr Imagesmentioning
confidence: 99%
“…128,129 In recent years, deep learning, particularly CNN, has gained substantial popularity in the MRI field for image reconstruction, image quality improvement, image transfer, disease detection, tissue segmentation, and classification. [130][131][132][133][134][135][136][137][138][139][140][141][142] Multiparametric MRI has been used for analyses using deep learning. Multiparametric MRI is potentially useful for lesion segmentation to fully capture the extent of the disease and has been used to segment cancers and multiple sclerosis plaques.…”
Section: Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…After 10 times cross-validation and independent testing, the results showed that in training, the accuracy of the MM-RF model was 0.849, and the AUC value was 0.826; for testing, the accuracy of the MM-RF model was 0.871, and the AUC value was 0.902. Hagiwara et al [38] constructed a convolution neural network model based on SqueezeNet to distinguish between NMO and MS. In this study, 35 patients with MS and 18 patients with NMO were enrolled, and left-over cross-validation (leave-one-out cross validation) was used to evaluate the performance of the model.…”
Section: A Back Propagation Neural Network Model With 17 Input Parame...mentioning
confidence: 99%